2020
DOI: 10.1001/jamanetworkopen.2019.20431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Informational Content and Readability of US Lung Cancer Screening Program Websites

Abstract: IMPORTANCE The internet is an important source of medical information for many patients and may have a key role in the education of patients about lung cancer screening (LCS). Although most LCS programs in the United States have informational websites, the accuracy, completeness, and readability of these websites have not previously been studied.OBJECTIVE To evaluate the informational content and readability of US LCS program websites. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study assessed US LCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Although SDM visits inclusive of decision aids are considered a component of highly effective LCS programs and are mandated by the U.S. Centers for Medicare and Medicaid Services (CMS) ( 60 , 61 ), currently available decision aids may not be appropriate for populations with limited health literacy. Most patient-facing websites with information about LCS are written above the recommended sixth-grade reading level advised by the American Medical Association and are largely written for English speakers ( 62 , 63 ). To ensure informed LCS decisions that are consistent with the patient’s preference, it is crucial that patients understand numeracy concepts for informed decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…Although SDM visits inclusive of decision aids are considered a component of highly effective LCS programs and are mandated by the U.S. Centers for Medicare and Medicaid Services (CMS) ( 60 , 61 ), currently available decision aids may not be appropriate for populations with limited health literacy. Most patient-facing websites with information about LCS are written above the recommended sixth-grade reading level advised by the American Medical Association and are largely written for English speakers ( 62 , 63 ). To ensure informed LCS decisions that are consistent with the patient’s preference, it is crucial that patients understand numeracy concepts for informed decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that assessed colorectal cancer screening online information reported that most materials surpassed the sixth-grade reading level [37,38], and the average reading level was 11th grade [38]. Studies that assessed lung cancer screening online information also reported that only a few of the evaluated materials had reading levels at or below a sixth-grade reading level [39,40], and the average level was 10th grade [40]. Thus, information on the HPV vaccination and cervical cancer, as well as information on other types of vaccines and cancer screening, is often written above the recommended sixth-grade reading level and is difficult to read.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Given the findings from this study, such interventions may include written education in the form of advertisements and materials in health clinics. Because many existing websites and written materials about LCS may not be well understood by the target audience, 43-46 content should be tested with the screening-eligible population to ensure comprehension.…”
Section: Discussionmentioning
confidence: 99%